Development of a cost-effective automated platform to produce human liver spheroids for basic and applied research. (28th October 2020) - Lucendo-Villarin, B; Meseguer-Ripolles, J; Drew, J; Fischer, L; Ma, E; Flint, O; Simpson, K J; Machesky, L M; Mountford, J C; Hay, D C
Abstract: Liver disease represents an increasing cause of global morbidity and mortality. Currently, liver transplant is the only treatment curative for end-stage liver disease. Donor organs cannot meet the demand and therefore scalable treatments and new disease models are required to improve clinical intervention. Pluripotent stem cells represent a renewable source of human tissue. Recent advances in three-dimensional cell culture have provided the field with more complex systems that better mimic liver physiology and function. Despite these improvements, current cell-based models are variable in performance and expensive to manufacture at scale. This is due, in part, to the use of poorly defined or cross-species materials within the process, severely affecting technology translation. To address this issue, we have developed an automated and economical platform to produce liver tissue at scale for modelling disease and small molecule screening. Stem cell derived liver spheres were formed by combining hepatic progenitors with endothelial cells and stellate cells, in the ratios found within the liver. The resulting tissue permitted the study of human liver biology 'in the dish' and could be scaled for screening. In summary, we have developed an automated differentiation system that permits reliable self-assembly of human liver tissue for biomedical application. Going forward we believe that this technology will not only serve as an in vitro resource, and may have an important role to play in supporting failing liver function in humans.